ANALYSIS OF SALMONELLA SPP. DETECTIONS IN EUROPEAN UNION COUNTRIES ACCORDING TO RASFF DATABASE - S. Ye. Smajhel; N. B. Shadrova (Ветеринария сегодня)
Ofcial data of RASFF (Rapid Alert System for Food and Feed) database on detection of Salmonella spp. in animal and plant raw materials in 2010–2015 are demonstrated. Total of 2,651 notifcations of Salmonella spp. detection were reported by RASFF member countries. The majority of such notifcations are associated with contamination of poultry meat and poultry products, feed, fruits and vegetables. Salmonella can survive in food for a long time (up to 6 months). The cause of salmonellosis in humans mostly involves consumption of raw or insufciently heat-treated eggs, meat and milk products. Regulation (EU) No. 142/2011 prescribes a requirement, which the heat-treated and processed food products shall comply with, i.e. absence of Salmonella in 25 g of the product. Analysis of RASFF data for 2010–2015 demonstrated annual increase of Salmonella spp. detections. The most frequently occurring is Salmonella enterica. Over the above mentioned period there were notifcations of 154 Salmonella serovars, the overwhelming serovars include S. enterica – 32.4%; Salmonella spp. – 18.8%; S. enteritidis – 6.3%; S. typhimurium – 4.6%, S. Agona – 2.6%; S. Lexington – 1.4%. Salmonella spp. were detected in poultry meat (19.5%), in feed for dogs and cats (5.6%), in pork (3.7%), in fshmeal (5.1%). During the period from 2010 to 2014, the increase of Salmonella notifcations in plant feed was reported. Over 2010–2015, RASFF reported of 42 salmonellosis outbreaks that resulted in 1,586 diseased humans.